2016
DOI: 10.1007/s00464-016-4762-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of endoscopic balloon dilation for treatment of colorectal anastomotic stenosis

Abstract: Endoscopic balloon dilation is a safe approach to effectively relieve an anastomotic stenosis following a colorectal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 15 publications
3
32
4
Order By: Relevance
“…Previous studies have demonstrated that balloon dilation was a safe and effective procedure, with short-term recurrence rates ranging from 6-20% [16,17]. The largest series, which followed 76 patients for a median of 17 years, revealed a long-term success rate of 75% [3]. The present study had observed similar good outcomes, with a 100% primary success rate and a 17.5% recurrence rate.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Previous studies have demonstrated that balloon dilation was a safe and effective procedure, with short-term recurrence rates ranging from 6-20% [16,17]. The largest series, which followed 76 patients for a median of 17 years, revealed a long-term success rate of 75% [3]. The present study had observed similar good outcomes, with a 100% primary success rate and a 17.5% recurrence rate.…”
Section: Discussionsupporting
confidence: 77%
“…Our preliminary study found an incidence rate of 3.14% [12], which was as low as previous studies. Anastomotic strictures have previously been observed at a median of 5-12 months following colorectal surgery [3,13]. In the present study, anastomotic strictures occurred at a median of 7 months from the index surgery.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The initial success rate of balloon dilatation of postsurgical strictures is 91-100%, depending on the series [7,9]. Long-term follow-up studies show its effectiveness is maintained, avoiding the need for surgery in 75% of strictures [9,10], with a low rate of complications, around 15%, mostly minor (such as mild bleeding) that can generally be managed conservatively. A recent review of 850 procedures [11] estimated the overall rate of perforation with this technique at 1.1%.…”
Section: Dilatationmentioning
confidence: 99%